Response Functions in Disasters: Iran Flash Flood 2016. (December 2019) - Dizaji, Reza Abbaszadeh; Ardalan, Ali; Fatemi, Farin
ABSTRACT: Objective: Heavy rain and flash flooding left behind a trail of disaster in the western and south-western provinces of Iran in April 2016. The purpose of this study is to highlight the response functions that should be undertaken when such disasters strike. Methods: Secondary data, such as documents, organizational reports, and forms completed during response to the flood visits, were the methods of data collection in this study. Then, collected data were analyzed according to the response functions to disasters. Results: The study found that a strong disaster response function was the early warning system, by the Iran Meteorological Organization, announced 1 week before the flood. Weaker functions were the lack of coordination among response organizations and the lack of a safety officer in the Incident Command System structure during the flash flood. Conclusions: The list of the disaster response functions identified by this study should aid the decision makers and first responders in facing natural or man-made disasters and enable them to better prepare for response functions in the future disasters.